Vitamin D Status Among Children aged 2 months to 13 years-a Hospital Based Study - Rimal, Hem Sagar; Walavalkar, Shripad J (Birat Journal of Health Sciences, 2018)
Introduction: Vitamin D is an important micronutrient having crucial role in calcium and phosphate homeostasis but there is emerging evidence to suggest its role in prevention of infectious, inflammatory and neoplastic diseases. The vitamin D insufficiency/deficiency is a widely recognized problem among children in developed as well as developing countries. Objective: To find out the prevalence of vitamin D deficiency/insufficiency among children aged 2 months to 13 yrs and its correlation with serum calcium, phosphate and demographic factors. Methodology: Prospective, cross sectional, hospital based study conducted at Birat Medical College Teaching Hospital for a period of one year among children presented to pediatric OPD in whom pediatrician had a suspicion of Vitamin D Insufficiency /Deficiency. Venous blood Samples were taken for the estimation of 25(OH) Vitamin D, Calcium and Phosphate. Statistical analysis was done using SPSS software version 16. Results Among 174 children aged 2 months to 13 years, the prevalence of vitamin D insufficiency at the cutoff of <30ng/ml was 82.75% where as no cases of vitamin D deficiency was noted at cut off level of < 10 ng/ml. Children residing in urban area, samples taken in the winter season had higher prevalence of vitamin D insufficiency (p value <0.05). Serum calcium and phosphate level were found positively correlated with Vitamin D level (p<.05). However the relationship was very strong between Vitamin D and Calcium (r=0.402, p-value <0.001) and weak positive correlation was noted with phosphate(r=0.155, p value <0.05). Conclusion: There is very high prevalence of Vitamin D insufficiency among children. The vitamin D insufficiency was significantly higher in winter season as compared to summer. Children living in the urban area are more prone to Vitamin D insufficiency. Moderately strong positive correlation was observed between Vitamin D level and calcium but weak correlation existed with phosphate. BJHS 2018;3(1)5 : 381-384